Spectrophotometer and Beer-Lambert Law - Li, Haoxuan (Transactions on Environment, Energy and Earth Sciences, 2026)
This study was designed to investigate the relationship between the concentration of aqueous copper (II) sulfate (CuSO4) solutions and their light absorbance, and to validate the Beer-Lambert Law for quantitative analysis. A series of standard solutions, with concentrations from 0.0131 M to 0.510 M, were prepared by serially diluting a stock solution. We measured the absorbance of each solution at a wavelength of 640 nm with a UV-visible spectrophotometer. The resulting data showed a strong linear relationship (y=2.2344x−0.0084, with an R2 value of 0.9996). Using this calibration, we determined the concentration of an unknown CuSO4 solution to be 0.453 M, differing from its theoretical concentration by a minimal error of just 0.658%. These results confirm that the Beer-Lambert Law is both applicable and accurate for this chemical system in the tested range.
Keywords: Beer-Lambert Law; Spectrophotometry; Copper(II) Sulfate; Quantitative Analysis.